Legal Protection of Insurance Policyholders of PT Aspan Medan in the Revocation of Business License by the Financial Services Authority Institution - Kumala Sari Nasution; Adlin Budhiawan (Warmadewa Press, 2024)
Public trust in insurance companies is growing rapidly, as shown by the amount of premiums successfully collected by insurance companies. Therefore, insurance companies must improve their performance to support public trust in insurance. The life insurance firm Aspan Medan Company lost its business license from Financial Services Authority. Financial Services Authority roles, functions, and authority are the study's issues. Impact of Financial Services Authority insurance business license revocation on parties' mechanisms, rights, and duties Juridical examination of Financial Services Authority insurance company license revocation According to Insurance Law 40 of 2014, Descriptive legal research employs normative and empirical methods. Literature-based qualitative data analysis. Financial Services Authority regulates and supervises banks. Bank health regulation and monitoring. Bank prudential regulation and oversight. Mechanisms, rights, and duties of parties affected by Financial Services Authority insurance business license revocation. Financial Services Authority insurance company license revocation process A member of the Financial Services Authority Board of Commissioners and the Chief Executive Officer of the Nonbank Financial Industry Supervisor approve the letter of revocation of an insurance business license, transferring all rights and obligations to third parties, creditors, and policyholders. Juridical review of the Financial Services Authority's revocation of an insurance business license under Insurance Law Number 40 of 2014. If the Financial Services Authority believes the Insurance Company's condition endangers Policyholders, Insured, or Participants, it may revoke business licenses without other administrative sanctions.